2021
DOI: 10.1016/j.jseint.2021.06.003
|View full text |Cite
|
Sign up to set email alerts
|

Prior shoulder surgery and rheumatoid arthritis increase early risk of infection after primary reverse total shoulder arthroplasty

Abstract: Background Reverse total shoulder arthroplasty (RTSA) has become an increasingly popular surgery for patients with rotator cuff arthropathy, unreconstructible proximal humeral fracture, and end-stage glenohumeral arthritis. The increased annual volume of RTSAs has resulted in more postoperative complications and revision rates between 3.3% and 10.1%. Postoperative infection is one of the most common complications requiring revision surgery after primary RTSA. This study assesses patient-specific r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 28 publications
0
9
0
Order By: Relevance
“…Four studies [ 22 , 23 , 26 , 29 ] could be used for analyses with previous non arthroplasty surgery history. The results indicated that patients with surgical history are at more risk than the control group.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Four studies [ 22 , 23 , 26 , 29 ] could be used for analyses with previous non arthroplasty surgery history. The results indicated that patients with surgical history are at more risk than the control group.…”
Section: Resultsmentioning
confidence: 99%
“…One study [ 22 ] included aTSA and rTSA only, and another study [ 30 ] included aTSA and HA only. Four studies [ 21 , 23 , 25 , 29 ] were recorded for only one type of operation. In the remaining three studies [ 27 , 28 , 30 ], there was no detailed description of whether TSA was anatomical or reversed.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations